An Essay on the Relationship Between an Actor’s Body and Their Fictional Character in the Context of Merleau-Ponty’s Phenomenology of Embodiment - Tuğçe Gözde Pelister (Tiyatro Eleştirmenliği ve Dramaturji Bölümü Dergisi)
This article discusses the actor’s body as a philosophical phenomenon based on French philosopher Maurice Merleau-Ponty’s phenomenology of body and perception, which argues that the body gives meaning to the mind, and the mind gives meaning to the body. This discussion takes place in the reciprocity between the actor’s body and their embodiment of a fictional character. The philosophical inquiry into the actor’s body is linked to the perception and orientation relationship between the actor’s body and the fictional character. Moreover, as the living body and subject, the actor encounters and intertwines with the character on the spatial stage of the play. While the actor’s body turns into the body of the fictional character on stage, the actor’s living body phenomenologically becomes invisible. Additionally, the fictional character, who never actually existed, becomes embodied in the actor’s temporarily absent body.